Spatial Analysis of Inclusive Growth in Central Java Province - Farid Adam Rahmadi; Ernan Rustiadi; Dedi Budiman Hakim (Jurnal Manajemen dan Agribisnis, 2025)
Background: Economic growth, while often viewed as a sign of development success, may not guarantee equitable income distribution, particularly in developing nations. The Inclusive Economic Development Index (IPEI) by the National Development Agency (Bappenas) gauges inclusivity in Indonesian development. In Central Java Province, regency/city-level IPEI varies, indicating uneven growth. Purpose: This study has two objectives: (1) to analyze the spatial distribution patterns of inclusive growth in regencies/cities within Central Java Province; and (2) to assess the relevance of the regional development system by considering the spatial interrelations of inclusive growth. Design/methodology/approach: The research utilizes secondary data. The same analytical methods are applied for both objectives with different data points Moran's Index Analysis, Moran’s Scatterplot, and Local Indicator of Spatial Autocorrelation (LISA). Findings/Results: The research findings indicate that (1) the spatial distribution pattern of the IPEI in the regencies/cities of Central Java Province from 2012 to 2021 tends to form spatial clusters, with three regencies/cities showing significant and consistent local IPEI spatial influence namely Surakarta City (High-High quadrant) and Banjarnegara and Wonosobo (Low-Low quadrant), and (2) alternative Regional Development (WP) spatial analysis reveals a high IPEI spatial correlation within each WP, with Surakarta City and Salatiga City consistently appearing in the High-High quadrant, while Pekalongan City is significantly positioned in the Low-Low quadrant. Conclusion: The spatial distribution pattern of the IPEI in Central Java Province tends to form spatial clusters with three regencies/cities showing significant and consistent local IPEI spatial influence namely Surakarta City, Banjarnegara, and Wonosobo. The spatial analysis of alternative WPs reveals a strong spatial correlation of IPEI values with Surakarta City and Salatiga City identified as significant local spatial influencers.Originality/value (State of the art): This study enables the identification of regencies, cities, and/or WP with lagging IPEI values, thereby allowing policymakers to design targeted interventions. Based on the findings, Banjarnegara and Wonosobo are identified as such areas. The alternative WPs proposed in this study can serve as important considerations for regional development planning in Central Java Province. Keywords: IPEI, inclusive growth, spatial analysis, Moran’s Analysis, Central Java Province